Some New Results on Fixed Points of Meromorphic Functions Defined in Annuli - Zhaojun Wu; Zuxing Xuan; Yuxian Chen (Journal of Function Spaces)
The purpose of this paper is to investigate the fixed points of meromorphic functions in annuli. Some well-known facts of fixed points for meromorphic functions in the plane will be considered in annuli.